2018
DOI: 10.1007/978-3-319-92961-3
|View full text |Cite
|
Sign up to set email alerts
|

Servant-Leaders in Training

Abstract: By way of primary go-to-platform, this Series precisely maps the terrain of the twin fields of Workplace Spirituality and Fulfillment in the disciplines of business, psychology, health care, education, and various other allied fields. It reclaims the sacredness of work-work that is mind-enriching, heartfulfilling, soul-satisfying and financially-rewarding. It fills the gap in scholarship in the allied disciplines of Workplace Spirituality and Flourishing. Using a comprehensive schema, it invites contributions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 0 publications
0
11
0
2
Order By: Relevance
“…Not surprisingly, managers are trained to practice the servant leadership style (Horsman, 2018). However, our theory points out an unintended consequence of servant leadership on emotional exhaustion.…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…Not surprisingly, managers are trained to practice the servant leadership style (Horsman, 2018). However, our theory points out an unintended consequence of servant leadership on emotional exhaustion.…”
Section: Introductionmentioning
confidence: 82%
“…A recent meta‐analysis of 130 independent studies demonstrated that servant leadership predicted behavioral outcomes over and beyond a combination of transformational, ethical, and authentic leadership (Lee et al, 2020). Not surprisingly, managers are trained to practice the servant leadership style (Horsman, 2018). However, our theory points out an unintended consequence of servant leadership on emotional exhaustion.…”
Section: Introductionmentioning
confidence: 99%
“…(p. 41) Servant-leadership, a non-traditional leadership theory, shifts the spotlight away from the leader at the center and repositions it towards others. Stemming from the belief that natural leaders are called to serve others first, and only come to lead at a later point, Horsman (2019) equates this outward motivation of servant-leaders to an initial inward sense of fulfillment and actualization. Horsman sees this desire to see others grow, to invest fully in their well-being, at the heart of servantleadership.…”
Section: Self-transcendencementioning
confidence: 99%
“…Dalam upaya mereka untuk membuat survei untuk mengukur kepemimpinan pelayan, van Dierendonck dan Nuijten (2011) mengoperasionalkan pemimpin pelayan sebagai seseorang yang etis dan berpusat pada orang dalam bagaimana mereka memimpin (pemberdayaan, akuntabilitas, keberanian, dan pengawasan), melayani (berdiri mundur) , kerendahan hati, dan keaslian), dan kemampuan untuk memaafkan. Brutus dan Vanhove (2017) menyarankan enam kompetensi kepemimpinan pelayan yang mencakup aspek menjadi manajer yang baik serta layanan (mengutamakan pengikut), pemberdayaan (menanamkan rasa kompetensi dalam pengikut melalui komitmen terhadap pengembangan pribadi dan profesional), menciptakan visi dan arahan, penatalayanan (meninggalkan organisasi dalam kondisi yang lebih baik daripada sebelumnya), integritas, dan penghargaan antarpribadi (Horsman, 2018).…”
Section: Hasil Dan Pembahasanunclassified
“…Dengan definisidefinisi ini, ada banyak minat mengenai hubungan kesadaran-diri, nauthentisitas, moralitas, cinta, kepercayaan, dan spiritualitas dengan kepemimpinan yang melayani. Gagasan tentang topik ini akan ditawarkan secara lebih rinci (Horsman, 2018).…”
Section: Hasil Dan Pembahasanunclassified